The Role of Human Activities in Climate Change: Exploring the Link between Human Activities and Climate Change (Journal of Advances and Scholarly Researches in Allied Education, 2019)
There is overpowering proof that human activities, particularly consuming petroleum derivatives, are prompting expanded dimensions of carbon dioxide and other ozone harming substances in the climate, which thusly enhance the regular nursery impact, causing the temperature of the Earth's air, sea, and land surface to increment. The all around archived pattern of expanding of CO2 in the climate is brought about by the consuming of petroleum derivatives and gigantic land spread changes. The conclusive evidence that demonstrates unmistakably that human activities are in charge of ongoing increments in carbon dioxide in the environment is given via carbon isotopes (carbon molecules of various nuclear weight). These isotopes enable researchers to unique finger impression the wellspring of the carbon dioxide particles, which uncover that the expanded CO2 in the air is brought about by non-renewable energy source consuming